Neurodevelopmental evaluation for school-age children with congenital heart disease: recommendations from the cardiac neurodevelopmental outcome collaborative - Ilardi, Dawn; Sanz, Jacqueline H.; Cassidy, Adam R.; Sananes, Renee; Rollins, Caitlin K.; Ullman Shade, Catherine; Carroll, Gretchen; Bellinger, David C. (Cardiology in the young, 2020)
In 2012, the American Heart Association and the American Academy of Paediatrics released a scientific statement with guidelines for the evaluation and management of the neurodevelopmental needs of children with CHD. Decades of outcome research now highlight a range of cognitive, learning, motor, and psychosocial vulnerabilities affecting individuals with CHD across the lifespan. The number of institutions with Cardiac Neurodevelopmental Follow-Up Programmes and services for CHD is growing worldwide. This manuscript provides an expanded set of neurodevelopmental evaluation strategies and considerations for professionals working with school-age children with CHD. Recommendations begin with the referral process and access to the evaluation, the importance of considering medical risk factors (e.g., genetic disorders, neuroimaging), and the initial clinical interview with the family. The neurodevelopmental evaluation should take into account both family and patient factors, including the child/family’s primary language, country of origin, and other cultural factors, as well as critical stages in development that place the child at higher risk. Domains of assessment are reviewed with emphasis on target areas in need of evaluation based on current outcome research with CHD. Finally, current recommendations are made for assessment batteries using a brief core battery and an extended comprehensive clinical battery. Consistent use of a recommended assessment battery will increase opportunities for research collaborations, and ultimately help improve the quality of care for families and children with CHD.